Antifreeze Proteins: A Tale of Evolution From Origin to Energy Applications - Gharib, Ghazaleh; Saeidiharzand, Shaghayegh; Sadaghiani, Abdolali K.; Koşar, Ali (Frontiers in Bioengineering and Biotechnology, 2022)
Icing and formation of ice crystals is a major obstacle against applications ranging from energy systems to transportation and aviation. Icing not only introduces excess thermal resistance, but it also reduces the safety in operating systems. Many organisms living under harsh climate and subzero temperature conditions have developed extraordinary survival strategies to avoid or delay ice crystal formation. There are several types of antifreeze glycoproteins with ice-binding ability to hamper ice growth, ice nucleation, and recrystallization. Scientists adopted similar approaches to utilize a new generation of engineered antifreeze and ice-binding proteins as bio cryoprotective agents for preservation and industrial applications. There are numerous types of antifreeze proteins (AFPs) categorized according to their structures and functions. The main challenge in employing such biomolecules on industrial surfaces is the stabilization/coating with high efficiency. In this review, we discuss various classes of antifreeze proteins. Our particular focus is on the elaboration of potential industrial applications of anti-freeze polypeptides.